Resemiotisation from page to stage: translanguaging and the trajectory of a musilingual youth's poem. Issue 1 (2nd January 2020) - Moore, Emilee; Bradley, Jessica
ABSTRACT: This article reports on part of an ethnographic research project undertaken over a period of 20 months in Leeds, UK, with a youth spoken word (YSW) poetry organisation. The research focused on the fluid practices in which the youth engage that span spoken, written, visual, gestural, digital, musical and spatial modes, and across times and places. Given its inherent fluidities, YSW is a particularly interesting practice for studying semiosis. Among other aspects, the research focused on the trajectories of poems written and performed by youth and the semiotic transformations they undergo across time and space. The article explores how resemiotisation sheds light on the complexities of the transformations that one particular poem undergoes as it travels. It focuses on a poem titled 'To Him', written and performed by a 17-year old poet. The main arguments put forward are that: (1) translanguaging is a more comprehensive term than others for describing how the poet engages her communicative repertoire; (2) resemiotisation is both a lens for conceptualising translanguaging, and an indispensable analytical process in the case of the data studied for understanding the complexities of the poet's meaning-making practices. Looking beyond our own discipline and making use of musical annotation, we contend that focusing solely on spoken and written language would be insufficient to gauge the complexity of the meaning-making process undertaken by the young poet.